1997
DOI: 10.1111/j.1540-8159.1997.tb05489.x
|View full text |Cite
|
Sign up to set email alerts
|

Syncope: The Diagnostic Value of Head‐Up Tilt Testing

Abstract: To determine the usefulness of prolonged head-up tilt in the diagnosis of neurally mediated syncope, 201 patients with history of syncope of unknown cause and 102 age and gender matched control subjects underwent a 40 minute 60 degrees head-up tilt test. Head-up tilt elicited syncope (i.e., was positive) in 74 of the 201 patients (37%) with a history of unexplained syncope and in only 6 of the 102 controls (6%). The specificity of the test was 100% in patients 60 years of age and older. Symptoms during tilt-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Provocative maneuvers are more likely to result in syncope or arrhythmias that might require intervention or resuscitation. Studies that assessed the diagnostic value of HUT in evaluation of syncope (not dizziness alone) without provocative maneuver were conducted for 40 to 60 minutes and were shown to have a sensitivity and specificity of 37% to 67% and 90% to 94%, respectively (19,20). Similar studies assessing HUT with isoproterenol or nitrate challenge were conducted for 10 to 30 minutes and were determined to have sensitivity and specificity of 53% to 61% and 89% to 93%, respectively (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Provocative maneuvers are more likely to result in syncope or arrhythmias that might require intervention or resuscitation. Studies that assessed the diagnostic value of HUT in evaluation of syncope (not dizziness alone) without provocative maneuver were conducted for 40 to 60 minutes and were shown to have a sensitivity and specificity of 37% to 67% and 90% to 94%, respectively (19,20). Similar studies assessing HUT with isoproterenol or nitrate challenge were conducted for 10 to 30 minutes and were determined to have sensitivity and specificity of 53% to 61% and 89% to 93%, respectively (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a "gold standard" to diagnose neurocardiogenic syncope results in difficulties in establishing the sensitivity of TTT [13][14][15][16][17][18] . In a review of 12 published reports of studies involving 333 patients that underwent passive TTT, Pavri et al 19 reported that the positivity rate varies from 7% to 55% (mean of 24%).…”
Section: Discussionmentioning
confidence: 99%
“…However, results in other and larger studies varied between centers [25] which used different protocols, with or without pharmacologic provocation, and enrolled different populations. For example, in patients with syncope without a history of classical prodrome and triggers to suggest reflex syncope or evidence of significant heart disease to indicate cardiac syncope (i. e., unexplained syncope), a study showed that tilting without medication triggered reflex syncope in 37 % of subjects (74 of 201), compared to 6 % in controls (6 of 102) [42]. This suggests that a third of unexplained syncope could potentially be reflex syncope.…”
Section: Diagnosing Reflex Syncope: Methodological Issuesmentioning
confidence: 95%